Efforts to Improve Hygiene for Making Soybean Tempe - Suprajitno, Suprajitno; Mugianti, Sri (Journal of Community Service for Health, 2022)
The hygiene of soybean tempe processing begins with the selection of soybeans, the use of boiling facilities, and the use of water. The purpose of this activity was to improve the hygiene of making soybean tempe. The activities carried out were identification of needs and interventions. The target of the activity was the soybean tempe maker of Kel. Bendo Kec. Kepanjen Kidul of Blitar City. The activities were carried out on February – April 2022. The efforts made in the program were replacing the boiling facilities made of stainless steel, giving Chlorine 70% tablets to water sources, and Chlorine powder 40% to water reservoirs. The results of these efforts were the number of e-colli in the water after intervention dropped to 2 MPN/100 mL, odorless boiled water, ferrite tasteless soybeans, and tempe becomes more durable